Study on Effects of Blending Fiber Type and Ratio on Antibacterial Properties of Chitosan Blended Yarns and Fabrics - Tian, Xiao; Hua, Tao; Poon, Tszyin; Yang, Yiyi; Hu, Hong; Fu, Jimin; Li, Jianhui; Niu, Ben (Fibers and polymers, 2022)
Chitosan fiber possesses inherent advantages, such as excellent biocompatibility, nontoxicity as well as antibacterial property. However, there is no systematic study on the chitosan fiber blending effect with other fibers, and on that basis, there is no suitable fiber blending technology for yarn and fabric production, which results in the incorrect proportion of chitosan fiber blended with other fiber type and thus lowers the fabric functionality as well as increases the material cost. In this study, thirteen chitosan blended yarns were designed and developed. Blending yarn structure was examined and the effects of blending fiber type and ratio on the antibacterial and physical property were firstly investigated. The experimental results show that the inhibition rate rises with the increase of the chitosan blending ratio. The polyester/cotton/chitosan and tencel/chitosan yarns have a better inhibition rate of Staphylococcus than that of the cotton/chitosan yarn, indicating that the blending fiber type has an impact on antibacterial properties. Moreover, various chitosan blended knitted fabrics were produced by using the chitosan blended yarns developed and their antibacterial, physical properties and comfort as well as anti-mite activity were evaluated. The results illustrate that the knitted fabrics with a small amount of chitosan fibers exhibit excellent antibacterial properties and desirable comfort. Furthermore, the chitosan blended fabrics present the anti-mites effect. This work would contribute to lowering the material cost of functional yarns and promoting the development of antibacterial textiles.